3√3 (5 + 3√2 )
Answer: 15√3 + 9√6
Step-by-step explanation:
3√3 (5 + 3√2 )
= 3√3 x 5 + 3√3 x 3√2 (Apply the distributive rule. a(b+c) = ab+ac)
= 15√3 + 9√6 (Multiply the radicands, then multiply the constants. No mixing)
Answer: The simplified form of the given equation is
Step-by-step explanation:
From the given information, the numerator of the given fraction is:
and denominator of the given fraction is
The fraction becomes:
Applying middle term factorization in the numerator and denominator term, we get:
=
=
=
Cancelling (2z-5) factor from numerator an denominator, we get:
=
The above fraction is the simplified form of the equation formed in the question.
Answer:
1192 ft²
Step-by-step explanation:
Figure 3 is a trapezoidal prism.
The total surface area of a trapezoidal prism is made up of 2 congruent trapezoid bases and 4 rectangular faces connecting the bases.
The formula for the area of a trapezoid is:
where a and b are the bases, and h is the height.
From observation of the given diagram, the bases are 16 ft and 19 ft, and the height is 12 ft. Therefore, the area of each trapezoid base is:
To calculate the areas of all the rectangular faces, we first need to calculate the slant (s) of the trapezoid base by using the Pythagoras Theorem:
The area of a rectangle is the product of its width and length.
Therefore, the sum of the areas of the rectangular faces is:
To find the total surface area of the given trapezoidal prism, sum the area of the two trapezoid bases and the area of the rectangular faces:
Therefore, the total surface area of the given trapezoidal prism is 1192 ft², rounded to the nearest foot.
11,508
11,919
12,330
Answer:
11,919
Step-by-step explanation:
took the test
Answer:
2
Step-by-step explanation:
Convert mixed fraction to improper fraction
÷ ÷
Answer:
2
Step-by-step explanation:
Simplify the following:
(-(2 + 2/3))/(-(1 + 1/3))
(-(2 + 2/3))/(-(1 + 1/3)) = (-1)/(-1)×(2 + 2/3)/(1 + 1/3) = (2 + 2/3)/(1 + 1/3):
(2 + 2/3)/(1 + 1/3)
Put 1 + 1/3 over the common denominator 3. 1 + 1/3 = 3/3 + 1/3:
(2 + 2/3)/(3/3 + 1/3)
3/3 + 1/3 = (3 + 1)/3:
(2 + 2/3)/((3 + 1)/3)
3 + 1 = 4:
(2 + 2/3)/(4/3)
Put 2 + 2/3 over the common denominator 3. 2 + 2/3 = (3×2)/3 + 2/3:
((3×2)/3 + 2/3)/(4/3)
3×2 = 6:
(6/3 + 2/3)/(4/3)
6/3 + 2/3 = (6 + 2)/3:
((6 + 2)/3)/(4/3)
6 + 2 = 8:
(8/3)/(4/3)
Multiply the numerator by the reciprocal of the denominator, (8/3)/(4/3) = 8/3×3/4:
(8×3)/(3×4)
(8×3)/(3×4) = 3/3×8/4 = 8/4:
8/4
The gcd of 8 and 4 is 4, so 8/4 = (4×2)/(4×1) = 4/4×2 = 2:
Answer: 2